GAMBARAN POLA MAKAN DAN STATUS GIZI IBU HAMIL DI WILAYAH KERJA PUSKESMAS BUHIT KECAMATAN PANGURURAN KABUPATEN SAMOSIR TAHUN 2014 - JUSPEN PERY SIMARMATA; Albiner Siagian; Mhd.Arifin Siregar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
In the pregnancy phase, a pregnant need food with content of different nutrients and a fulfill of nutrient that much bigger than before. One of problem that surface cause of undernutrition is energy chronic malnutrition which is recognized by size of upper arm circumference <23,5 cm that be found in Kabupaten Samosir Puskesmas Buhit work area. The purpose of this research is to find out diet of kind of food and food frequence, the number of energy and protein adequacy and the nutritional status of pregnant women in Puskesmas Buhit work area. This is a descriptive research with cross sectional design. Technic sampling in this research is simple random sampling. This research did on August 2014 located in Puskesmas Buhit work area, Kecamatan Pangururan with 74 of pregnant sample. This research takes the diet of kind of food and food frequence, the number of energy and protein adequacy and nutritional status data were analyzed by univariate to get the frequency distributions. The research shows that most of the nutritional status of pregnant women based on Upper Arm Circle did not have a high risk in Energy Chronic Malnutrition (>23,5 cm) is about 94,6%. Adequacy of energy in pregnant women shows 47,3% in medium category and adequacy of protein in pregnant women shows 45,9% in low category. It is required to pregnant women to pay attention her diet and give some information about nutrient, pregnancy and the influence of nutrient for pregnancy through health promotion that handle with health servant. Keywords: diet, nutritional status, pregnant women